Menerapkan Model Accelerated Learning dalam Pembelajaran Akuntansi: Sebuah Pedoman untuk Dosen-Dosen Akuntansi - Se Tin (Media Riset Akuntansi, Auditing & Informasi, 2006)
This article aims to give understanding about how learning with accelerated learning approach is very important and explain how to designed accountancy subject with accelerated learning approach. The outline emphasize at three things. First, concept of accelerated learning. Second, model of acceleratedleaming. Third, usage of accelerated learning model in designing study of accountancy in class. Accelerated learning model in this article emphasize at emotional side of student. There is four keywords of accelerated learning model (grow, doing, named, demonstrate, repeat and celebrate). This model is result of collaborated between quantum teaching mode! (1999) and genius learning strategy model (2003).Keywords: accelerated learning, pm, doing, named, demonstrate, repeat, celebrate